From world cafes to road shows: using a mix of knowledge sharing approaches to improve wastewater use in urban agriculture - Amoah, Philip; Drechsel, Pay; Schuetz, Tonya; Kranjac-Berisavljevic, Gordana; Manning-Thomas, Nadia (Informa UK Limited, 2009)
This paper documents the application of several innovative knowledge sharing approaches and some of the lessons learnt in a project addressing food safety concerns deriving from wastewater irrigated vegetables in Ghana. Knowledge sharing activities received particular attention in the project to facilitate its impact pathway, in particular to (i) verify preliminary research messages on good practices, (ii) raise awareness and build capacity, and (iii) equip various stakeholder groups with knowledge, skills and materials. Key approaches and tools applied were the world caf? approach for the verification of research messages. The approach brought together farmers, traders and street food vendors to openly discuss proposed improvements in current practices and their potential for wider uptake. For targetoriented message dissemination multi-media training materials were prepared following recommendations from the intended users, like extension agents, catering and farmer field schools. The materials made use of local-language radio broadcasts, training and awareness videos, illustrated flip charts showing good and bad practices for wastewater use and improved teaching materials. Finally, for enhanced mutual learning so called road Shows were used to facilitate knowledge sharing between researchers, end-users, policy- and decision-makers. These allowed all stakeholders to follow the pathogen pathway from farm to fork while learning about the importance of well-identified intervention points and mutual responsibility. All applied approaches added significant value to the research work and facilitated its impact potential as first feedback shows. However, the applied tools do not come for free. They require careful preparations, the ability to listen and skillful facilitation.